IMPLIKASI FITRAH TERHADAP PENDIDIKAN - Ratna Sari; Habib Anwar Al Anshori (STKIP Subang, 2026)
Fitrah is a basic human potential that has been given since birth by Allah SWT. The concept of fitrah in Islamic education is an important foundation in forming human beings who have faith, knowledge, and noble character. This research aims to explain the nature of fitrah as the basis of education, identify aspects of fitrah that need to be developed, and analyze the implications of fitrah on the goals, roles of educators, and learning methods. The method used is a literature study by examining various Islamic educational literature. The results of the study show that education is not in charge of creating new potential, but rather developing the potential of nature that students already have. Therefore, education must be oriented towards the development of religious, intellectual, social, emotional, and physical aspects in a balanced manner in order to create a complete and characterful human being.